Indigenous Papuan Women Under Patriarchal Socio-Political Systems: Marginalization In International Relations And Indigenous Peoples Politics - Nurinaya Nurinaya; Karmila Sinen; Tri Handayani (Journal of Government Science Studies, 2026)
Issues concerning Indigenous women have gained increasing attention in global discussions on human rights and Indigenous Peoples. However, a significant gap persists in International Relations scholarship, particularly within Feminist International Relations, which has not systematically examined the lived experiences of Indigenous Papuan women within global Indigenous rights discourse. This study analyzes the forms of marginalization faced by Indigenous Papuan women in patriarchal social structures and explores how these experiences intersect with international Indigenous governance frameworks. Using a qualitative descriptive case study approach, data were collected through in-depth interviews, participatory observation, and analysis of academic and policy documents. The analysis draws on patriarchy theory, Feminist International Relations, and Indigenous rights frameworks. Findings show that Indigenous Papuan women experience multi-layered marginalization rooted in entrenched local patriarchal norms and reinforced by limited representation in global governance arenas. This is reflected in restricted decision-making power, limited access to land and economic resources, inadequate education and healthcare, and minimal formal leadership roles. Despite these constraints, they demonstrate resilience through community-based economic initiatives, land and environmental advocacy, legal literacy programs, and grassroots diplomacy.Theoretically, this study advances Feminist International Relations by positioning Indigenous women’s local experiences as constitutive of global politics and exposing how global governance reproduces intersectional marginalization.